Association Between Depressive Symptoms and Serum Brain-Derived Neurotrophic Factor Levels in Patients With First-Episode and Drug-Naïve Schizophrenia - Wu, Yuxuan; Du, Xiangdong; Yang, Ruchang; Yue, Yan; Peng, Ruijie; Wu, Siqi; Wang, Haitao; Zhou, Yue; Fang, Xiaojia; Yuan, Nian; Li, Ronghua; Zhang, Jun; et al. (Frontiers in Psychiatry, 2022)
Previous studies have shown that brain-derived neurotrophic factor (BDNF) levels are inversely associated with the severity of depressive symptoms and increase as depressive symptoms improve. There is also evidence that BDNF may be involved in the pathophysiology of schizophrenia. Therefore, the purpose of this study was to investigate the relationship between BDNF levels and depressive symptoms in patients with first episode and drug-naïve (FEDN) schizophrenia. We recruited a total of 90 patients with FEDN schizophrenia and 60 healthy controls. Psychopathological symptoms and depressive symptoms were measured by the Positive and Negative Syndrome Scale (PANSS) and the 17-item Hamilton Depression Scale (HAMD-17), respectively. Serum BDNF levels were assessed by sandwich enzyme linked immunosorbent assay in all participants. Serum BDNF levels were lower in patients with FEDN schizophrenia compared to healthy controls. Except for the negative subscale (p>0.05), patients with depressive symptoms had higher PANSS total score and two of the three subscales (p<0.05) than those without depressive symptoms. Moreover, patients with depressive symptoms had higher BDNF levels than those without depressive symptoms (p＜0.05). Furthermore, we found a significant association between BDNF levels and positive subscore (p < 0.01). However, there was no significant association between BDNF levels and HAMD scores (p＞0.05). Our findings suggest that FEDN schizophrenia patients with depressive symptoms have higher serum BDNF levels in the early stages of the disease. Low serum BDNF levels may be involved in the positive symptoms of FEDN schizophrenia, but not in depressive symptoms.